To Compare Reduction in Exacerbation of Severe COPD with Double Inhaled Therapy Plus Roflumilast Vs Double Inhaled Therapy Alone - Jahangir Ali , Rubina Aman ,Attiya Hameed , Hamza Masood (Journal of Islamic International Medical College)
Objective: To compare the efficacy of double inhaler therapy plus Roflumilast versus double inhaler therapy alone in reducing COPD exacerbations among patients with severe COPD. Study Design:Quasi experimental study. Place and Duration of Study: The study was conducted in Pulmonology department Pakistan Institute of Medical Sciences Islamabad, from 1-8-2019 to 1-8-2020. Materials and Methods: A total of 126 COPD (GOLD stage III and IV) patients, on dual inhaled therapy with Long-Acting Beta 2 Agonists (LABA) and Inhaled Corticosteroids (ICS), who had one or more acute exacerbation in the preceding year were included in the study. Patients were divided into two groups A & B. Group A was assigned dual inhaled therapy plus Roflumilast 500mcg once daily, and Group B, dual inhaled therapy alone. Forced Expiratory volume 1 (FEV1), 6 minutes' Walk Distance (6mWD), modified Medical Research Council Scale for dyspnea (mMRC dyspnea scale) and number of acute exacerbations were assessed at baseline, and at one , three, six, nine and twelve months of treatment and compared. SPSS version 21 was used for analyzing the data. Categorical variables were computed as frequency and percentage. Mean and Standard Deviation for numerical variables. Chi square test was used to compare frequencies of categorical variables and independent sample t-test for Mean. Level of Significant was taken at P ≤05. Results: Twelve m onths after the start of therapy, group A showed significant improvement in FEV1, 6MWD,mMRC scale and acute exacerbations compared to group B (p values = 008*, 0.001*and 0.04* respectively). Conclusion: Adding Roflumilast to dual inhaled therapy in severe COPD significantly improves lung functions, patients' functional status and frequency of acute exacerbations